The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.2196/17411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Validity and Utility of Wearable Technology for Continuously Monitoring Patients in a Hospital Setting: Systematic Review

Abstract: Background The term posthospital syndrome has been used to describe the condition in which older patients are transiently frail after hospitalization and have a high chance of readmission. Since low activity and poor sleep during hospital stay may contribute to posthospital syndrome, the continuous monitoring of such parameters by using affordable wearables may help to reduce the prevalence of this syndrome. Although there have been systematic reviews of wearables for physical activity monitoring i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Studies on the use of fitness trackers in a perioperative setting or among patients with multiple pre-existing diseases are rare [ 12 ] and, according to systematic reviews, also hampered by a high risk of bias [ 13 ] and suffer from low quality [ 14 ]. In particular, it has been shown that motion artifacts influence the mean absolute error (MAE) of the measurements by up to 30% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of fitness trackers in a perioperative setting or among patients with multiple pre-existing diseases are rare [ 12 ] and, according to systematic reviews, also hampered by a high risk of bias [ 13 ] and suffer from low quality [ 14 ]. In particular, it has been shown that motion artifacts influence the mean absolute error (MAE) of the measurements by up to 30% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wearable devices that can comfortably be worn on the body and perform several tasks in conjunction with handheld devices, such as smartphones, play a pivotal role in healthcare [6]. Recent systematic reviews have shown that wearable devices are useful for monitoring heart rate and sleep in hospital settings [7], increasing physical activity in children and adolescents [8], improving health-related outcomes in patients with cancer [9], and reducing body weight in individuals with obesity [10]. In addition, during the COVID-19 pandemic, sleep pattern and duration were accurately and effectively monitored by wearable devices [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…When implementing sensor-based measurements, choosing which devices to use or program is not trivial, as there are hundreds on the market. Moreover, many direct-to-consumer devices claim to accomplish similar things or perform similarly to SOTA devices without openly shared data or validation studies ( 271 273 ). Additionally, many devices come with their own out-of-the-box or off-the-shelf output metrics that are automatically computed for the user or consumer; care should be taken as to whether or not to take these metrics at face value (since many calculations are “black box” or proprietary and thus cannot be easily examined for noise, privacy, reliability, or accuracy) 16 ( 274 , 275 ).…”
Section: State-of-the-art In Pain Methodsmentioning
confidence: 99%